DOI: 10.31274/etd-180810-5727
|View full text |Cite
|
Sign up to set email alerts
|

From attitude to intent to action: Predictors of psychological help-seeking behavior among clinically distressed adults

Abstract: CHAPTER 1. INTRODUCTION CHAPTER 2. LITERATURE REVIEW Efficacy of Psychotherapy CHAPTER 2 LITERATURE REVIEW The number of individuals living with or at risk for developing a mental illness is staggering. Approximately one out of every four individuals experiences mental illness in a given year (Clement et al., 2015). Of those, approximately half are diagnosed with two or more disorders. In a recent study conducted by The World Health Organization (WHO), mental illness and suicide accounted for over fifteen perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 148 publications
(272 reference statements)
0
7
1
Order By: Relevance
“…This is consistent with theory of planned behavior (Ajzen & Fishbein, 1980), which posits that intentions ultimately predict behavior, and with help-seeking research that commonly uses intentions as an outcome, particularly when relationships are examined cross-sectionally (e.g., Chen, Romero, & Karver, 2016; Demyan & Anderson, 2012; Garriott, Raque-Bogdan, Yalango, Ziemer, & Utley, 2017; Lannin et al, 2015; Shechtman et al, 2018). The intentions measure we used has predicted help-seeking behavior among distressed community adults 2 weeks (Bitman-Heinrichs, 2017) and 3 months (Hammer & Spiker, 2018) later, but the predictive validity has not been examined with a general college sample. We recommend that future researchers assess the direct impact of emotional avoidance on help-seeking behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with theory of planned behavior (Ajzen & Fishbein, 1980), which posits that intentions ultimately predict behavior, and with help-seeking research that commonly uses intentions as an outcome, particularly when relationships are examined cross-sectionally (e.g., Chen, Romero, & Karver, 2016; Demyan & Anderson, 2012; Garriott, Raque-Bogdan, Yalango, Ziemer, & Utley, 2017; Lannin et al, 2015; Shechtman et al, 2018). The intentions measure we used has predicted help-seeking behavior among distressed community adults 2 weeks (Bitman-Heinrichs, 2017) and 3 months (Hammer & Spiker, 2018) later, but the predictive validity has not been examined with a general college sample. We recommend that future researchers assess the direct impact of emotional avoidance on help-seeking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Participants rate their likelihood of seeking help if they were experiencing each problem on a 4-point scale from 1 ( very unlikely ) to 4 ( very likely ). Demonstrating predictive evidence of validity, PIC scores have been positively linked to seeking help seeking among distressed community adults 2 weeks (Bitman-Heinrichs, 2017) and 3 months (Hammer & Spiker, 2018) later. This subscale has demonstrated internal consistency in previous undergraduate student samples (α = .90; Lannin et al, 2015), similar to the case in the current study (α = .89).…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Help-seeking for mental health problems during adolescence, when a majority of associated disorders emerge, has the capacity to generate better outcomes than intervention at any other time in the lifespan (Access Economics, 2009;Catania et al, 2011;Littlefield, 2008;ReachOut Australia & Mission Australia, 2018). Early intervention is the key to achieving successful mental health outcomes, reducing suicide rates and reducing the burden of mental disorders (Access Economics, 2009;Catania et al, 2011;Littlefield, 2008;ReachOut Australia & Mission Australia, 2018).…”
mentioning
confidence: 99%
“…The mental health help-seeking behaviors of psychiatric outpatients remain restricted despite that related studies have found factors such as willingness to seek professional help for a serious illness, feeling comfortable talking about personal problems with professionals, encouragement and pressure to seek help by family or friends, mental health literacy, self-concept, and employment status, as factors predicting mental health help-seeking behaviors among psychiatric outpatients (Mojtabai, et al 2016;Bitman-Heinrichs, 2017;Wigand, et al 2019;Egwuonwu, et al 2019). These submissions from related studies, therefore, creates a paucity of information on the predictive roles of perceived stigmatization and sociodemographic factors on mental health help-seeking behaviors among the population of interest.…”
Section: Introductionmentioning
confidence: 99%